2010
DOI: 10.1158/1940-6207.capr-09-0270
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Alterations Associated with Sulindac-Resistant Colon Tumors in ApcMin/+ Mice

Abstract: Although nonsteroidal anti-inflammatory drugs (NSAID), including sulindac, have been used extensively as chemopreventive agents for colorectal cancer, results are not consistent. NSAIDs, most reportedly sulindac, often do not cause a complete regression of adenomas and some patients develop resistance to NSAID treatment. In this study, we evaluated the effect of sulindac on colon tumorigenesis in the Apc Min/+ mouse model. Sulindac (180 ppm) given in drinking water for 9 weeks to Apc Min/+ mice significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 44 publications
0
20
1
Order By: Relevance
“…To address this possibility, Apc min/+ /CXCR2 WT and Apc min/+ /CXCR2 Het littermates were treated with a low‐dose sulindac (10 mg/kg/day) through a buffered drinking water for 9‐weeks from day 28 to 91 of their ages. Of note, many previous studies have used sulindac at doses higher than 20 mg/kg/day . While sulindac treatment and a single copy deletion of CXCR2 alone reduced total number of polyps in the small intestine by 31% and 19%, respectively, the combined conditions reduced the intestinal polyp formation by 57% (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…To address this possibility, Apc min/+ /CXCR2 WT and Apc min/+ /CXCR2 Het littermates were treated with a low‐dose sulindac (10 mg/kg/day) through a buffered drinking water for 9‐weeks from day 28 to 91 of their ages. Of note, many previous studies have used sulindac at doses higher than 20 mg/kg/day . While sulindac treatment and a single copy deletion of CXCR2 alone reduced total number of polyps in the small intestine by 31% and 19%, respectively, the combined conditions reduced the intestinal polyp formation by 57% (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…b ). We attribute this to the overall inefficiency in APC min ‐induced polyp formation in the large intestine, compared to the small intestine . We next studied the molecular mechanism underlying the inhibition of APC min ‐induced tumor formation by CXCR2 deletion.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate this possibility, colon tumors were examined immunohistochemically for PCNA staining (proliferation), and cleaved caspase-3, which detects an earlier stage of apoptosis in cells that have not yet undergone major morphological changes (14). A total of 10 colons from each genotype were selected for IHC analyses.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to be responsive to treatment with anti-inflammatory agents, including both anti-inflammatory dietary supplements as well as non-steroidal anti-inflammatory drugs (NSAIDs) [19]. For example, Greenspan et al reported that the NSAID Sulindac can decrease intestinal polyp number in the Apc Min/+ mouse that is associated with a decrease in proliferative and inflammatory prostaglandins in the small intestine and colon [27]. Similarly, another study reported that Celecoxib reduced the formation of intestinal polyps that was associated with lower levels of COX-2 activity [28].…”
Section: Discussionmentioning
confidence: 99%